Mediatisasi Dakwah Sufistik di TikTok: Adaptasi Spiritualitas dalam Budaya Digital - Panji Putrawan Makalalag; Deden Mauli Drajat; Budi Rahman Hakim (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study explores the dissemination of Sufi teachings through the TikTok account @Al.Amiin.id, highlighting how visual aesthetics, symbolism, and narrative techniques play a role in conveying spiritual messages to young audiences in the digital era. Using a qualitative approach with a critical case study strategy, this research analyses how elements such as colour, light, music, and spiritual metaphors are combined with reflective emotional narratives to preserve the depth of Sufi teachings. Drawing on Stig Hjarvard’s perspective on the mediatization of Religion, the study examines how social media not only functions as a channel for message dissemination but also reshapes religious practices and experiences. The findings reveal that @Al.Amiin.id successfully utilises the logic of digital media—such as short duration, visual aesthetics, algorithms, and trends—as instruments to present Sufism in the form of personal and easily comprehensible micro-narratives. This strategy demonstrates that Sufi preaching undergoes a process of mediatization, in which spiritual values are not merely transmitted but also reconstructed to align with the consumption patterns and cultural sensibilities of digital generations. The study further emphasises that despite the risks of commodification and simplification, Sufi preaching on social media can still preserve its spiritual depth through adaptive approaches. This research contributes to the study of how religious practices are transformed by digital media, offering a model of Sufi preaching that is communicative, inclusive, and relevant in the era of algorithms.